1991
DOI: 10.1063/1.105453
|View full text |Cite
|
Sign up to set email alerts
|

Quantum size microcrystals grown using organometallic vapor phase epitaxy

Abstract: Needle-shaped quantum size microcrystals as thin as 10 nm have been selectively grown by employing reduced pressure organometallic vapor phase epitaxy using trimethylgallium and arsine as source materials. The microcrystals grown within a SiO2 window area have their growth axes along the [111] direction. Transmission electron diffraction analysis shows that the crystal structure of microcrystals is consistent with the zinc-blende structure of GaAs. The mechanism for growing the needle-shaped crystals is simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 14 publications
4
82
0
1
Order By: Relevance
“…The understanding of the electronic and optical properties of impurities in these systems is a subject of scientific interest due to the possible technological applications in optoelectronics. GaAs-(Ga, Al)As QWWs are the most investigated systems, and a number of studies [3][4][5][6][7][8] concerned with impurity energy levels have been reported in the literature. Latgé et al [3] have calculated the ground and lowest excited states of a donor impurity in a cylindrical wire.…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of the electronic and optical properties of impurities in these systems is a subject of scientific interest due to the possible technological applications in optoelectronics. GaAs-(Ga, Al)As QWWs are the most investigated systems, and a number of studies [3][4][5][6][7][8] concerned with impurity energy levels have been reported in the literature. Latgé et al [3] have calculated the ground and lowest excited states of a donor impurity in a cylindrical wire.…”
Section: Introductionmentioning
confidence: 99%
“…In 1965, Holonyak Jr. et al extended this VLS method to III-V compound semiconductors by demonstrating the growth of GaP microwires [59]. In the early 90s, extensive and pioneering work was done by Hiruma et al on the VLS growth of III-V NWs using metal-organic vapor phase epitaxy (MOVPE) [60,61]. Along with the growth of regular ZB crystal phase, they demonstrated the possibility of other polytypes such as WZ in the case of InAs NWs [62].…”
Section: Nw Growth Mechanismsmentioning
confidence: 99%
“…Low-dimensional structures such as nanowires (NWs) have received strong interest beginning with the first demonstration in 1991 of synthesizing materials with a least one critical dimension with an extent of only 10-200 nm [1]. Their small diameters, often at distances of only a few times the interatomic distances in crystals, and their unique geometries lead to physical properties which differ drastically from the corresponding bulk material.…”
Section: Introductionmentioning
confidence: 99%